Inducing political action by workers. (23rd March 2015) - De Borger, Bruno; Glazer, Amihai
<x xml:space="preserve">Abstract</x> A firm aiming to influence a governmental policy may benefit from political action by its stakeholders, such as workers. This article studies the behavior of such a firm, showing that workers will have a greater incentive to engage in costly political activity against the governmental policy the greater their number and the higher the wage. The firm may, therefore, profit from paying above‐market wages and from hiring what might appear to be an inefficiently large number of workers. And because unions may overcome free‐rider problems of uncoordinated political effort, a firm may favor unionization, or be less opposed to unionization than it would otherwise be. The results of this article can also explain why firms may little reduce wages in a recession, and why the higher wages paid by unionized firms do not reduce survival rates of these firms.